Vasculature-on-a-chip platform with innate immunity enables identification of angiopoietin-1 derived peptide as a therapeutic for SARS-CoV-2 induced inflammation - Rick Xing Ze Lu; Benjamin Lai; Naimeh Rafatian; Dakota Gustafson; S. Campbell; Arinjay Banerjee; Robert Kozak; Karen Mossman; Samira Mubareka; Kathryn L. Howe; Jason E. Fish; Milica Radisic (2022)
Microfluidic polymeric blood vessel captures the adverse effects of SARS-CoV-2 on vasculature and enables identification of a therapeutic peptide that abolished virus induced cytokine storm orchestrated by the immune cells.